Redescription of the advertisement call of Brachycephalus tridactylus (Anura: Brachycephalidae) - Bornschein, Marcos R. [UNESP]; Rollo, Mario M. [UNESP]; Pie, Marcio R.; Confetti, André E.; Ribeiro, Luiz F. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
Miniaturized frogs of the genus Brachycephalus have restricted geographical distributions throughout the Atlantic Forest. Ecological data for most species are scarce and advertisement calls have been described for only 12 of the 36 known species, including B. tridactylus. The considerable duration of note length of the advertisement call of B. tridactylus has been mentioned in comparative studies of vocalizations in Brachycephalus. The single original recording of B. tridactylus, together with recordings made in March 2016 at the type locality, were analyzed to document any variation and redescribe the advertisement call of the species. In the recent recordings of B. tridactylus, the average length of the call is 50.8 s and the call is composed of 10-13 notes emitted at a note rate of 3.7-8.3 notes per min. The notes are isolated and composed of 1-3 pulses, with the note duration varying from 0.002-0.021 s. These values are not consistent with the original description of the call of B. tridactylus. The note duration is 89% shorter and the original description does not include notes with 1-3 pulses. The notes of B. tridactylus have few pulses, whereas those of B. ephippium have several. The advertisement call of B. tridactylus differs from that of B. albolineatus and B. mirissimus by having only isolated notes.
Keywords: Bioacoustics; Brazilian Atlantic Forest; Isolated notes; Note-centered approach